Perlindungan Hukum Bagi Pihak Ketiga (Natuurlijke Persoon) Berkaitan Dengan Adanya Actio Pauliana Dalam Hukum Kepailitan - Ida Ayu Putu Purnam Asri; I Nyoman Putu Budiartha; I Gusti Agung Ayu Gita Pritayanti Dinar (Jurnal Analogi Hukum, 2024)
When a bankrupt debtor transfers assets to a third party, actio pauliana becomes the creditor's legal remedy to recover the assets. For good faith third parties, the application of actio pauliana in bankruptcy becomes a legal polemic. This happens because the transfer of all or part of the debtor's assets will be withdrawn through actio pauliana. So that the problem arises "1) How is the enforcement of Actio Pauliana in Indonesia? and 2) How is the legal protection of third parties (natuurlijke persoon) in bankruptcy law related to the existence of actio pauliana?" This research seeks to understand the application of actio pauliana in Indonesia as well as the legal protection provided to third parties related to the existence of actio pauliana in bankruptcy law. The research methodology in this field is normative law. The application of Actio Pauliana has legal consequences, namely the third party losing the property that has been purchased from the debtor and canceling all legal actions that are not mandatory for the debtor to do which are detrimental to his creditors. Related to legal protection for the rights of third parties (Natuurlijke Persoon) due to Actio Pauliana, namely third parties can appear as concurrent creditors.